Some aspects of tissue water relations in cassava plant (Manihot esculenta Crantz) and their ecological interpretation - Palta, J.A. (International Center for Tropical Agriculture, 1980)
Two expt. were conducted to: (1) examine the application and other implications of the pressure/vol. technique (P/V) in the study of water stress in the cassava plant and (2) determine the relation of the water content in the tissue and its water potential. The P/V technique was used with branches of var. M Col 22 and M Mex 59 to determine the characteristics of water relations. Among the observations noted the following are found: the lack of considerable differences between the values of the relation between dry wt. and turgid wt. for stressed and unstressed leaves of the 2 cassava var. suggest that the amount of water in cell walls is closely related to the different proportions of the macromolecules (hemicellulose and pectic substances), rather than the thickness of the cell wall. The lowest and slowest decreases of the water content in the cell wall in M Col 22 (3.5 percent) compared to M Mex 59 (30 percent) suggests that the regulator capacity of the cell wall in M Col 22 may be an indicative factor of acclimatization to drought. On the hand, a higher intra-var. variation is indicated instead of a variation between the 2 var.The ability of the leaves of both var. studied is associated with the recovery of leaf area diminished under stress conditions. (CIAT)